Team creativity/innovation in culturally diverse teams: A meta‐analysis - Wang, Jie; Cheng, Grand H.‐L.; Chen, Tingting; Leung, Kwok (John Wiley and Sons Ltd, 2019)
This meta-analysis investigates the direction and strength of the relationship between diversity in culturally diverse teams and team creativity/innovation. We distinguish the effects of two diversity levels (i.e., surface- versus deep-level) in culturally diverse teams and examine the moderators suggested by the socio-technical systems framework (i.e., team virtuality and task characteristics in terms of task interdependence, complexity, and intellectiveness). Surface-level diversity in culturally diverse teams is not related to team creativity/innovation, while deep-level diversity in culturally diverse teams is positively related to team creativity/innovation. Moreover, surface-level diversity in culturally diverse teams and team creativity/innovation are negatively related for simple tasks, but unrelated for complex tasks. Deep-level diversity in culturally diverse teams and team creativity/innovation are positively related for collocated teams and interdependent tasks, but unrelated for non-collocated teams and independent tasks. We discuss the theoretical and practical implications.